Canadian Resources on Cannabis Use and Fertility, Pregnancy, and Lactation: Scoping Review - Ayni Sharif; Kira Bombay; Malia S Q Murphy; Rebecca K Murray; Lindsey Sikora; Kelly D Cobey; Daniel J Corsi (JMIR Publications, 2022)
BackgroundCannabis use among reproductive-aged Canadians is increasing, but our understanding of its impacts on fertility, pregnancy, and breast milk is still evolving. Despite the availability of many web-based resources, informed decision-making and patient counseling are challenging for expectant families and providers alike. ObjectiveWe aimed to conduct a scoping review of publicly available web-based Canadian resources to provide information on the effects of cannabis on fertility, pregnancy, and breast milk. MethodsFollowing PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews), we systematically searched 8 databases between January 1, 2010, and November 30, 2020, and web pages of 71 Canadian obstetrical, government, and public health organizations. We included English resources discussing the effects of cannabis on fertility, pregnancy, breastfeeding, or the exposed fetus and infant. Epidemiological characteristics, readability, and content information were extracted and summarized. ResultsA total of 183 resources met our inclusion criteria. Resources included content for public audiences (163/183, 89.1%) and health care providers (HCPs; 31/183, 16.9%). The resources were authored by national-level (46/183, 25.1%), provincial or territorial (65/183, 35.5%), and regional (72/183, 39.3%) organizations. All provinces and territories had at least one resource attributed to them. The majority (125/183, 68.3%) were written at a >10 grade reading level, and a few (7/183, 3.8%) were available in languages other than English or French. The breadth of content on fertility (55/183, 30.1%), pregnancy (173/183, 94.5%), and breast milk or breastfeeding (133/183, 72.7%) varied across resources. Common themes included citing a need for more research into the effects of cannabis on reproductive health and recommending that patients avoid or discontinue cannabis use. Although resources for providers were consistent in recommending patient counseling, resources targeting the public were less likely to encourage seeking advice from HCPs (23/163, 14.1%). ConclusionsCanadian resources consistently identify that there is no known safe amount of cannabis that can be consumed in the context of fertility, pregnancy, and breastfeeding. Areas of improvement include increasing readability and language accessibility and encouraging bidirectional communication between HCPs and patients. International Registered Report Identifier (IRRID)RR2-10.1136/bmjopen-2020-045006